Characteristic and source quantification of nitrogen in sediments of a subtropical mangrove estuary - Tan, Qingbi; Zhong, Yuhang; Sun, Siqi; Luo, Yongjun; Niu, Lixia (Frontiers in Marine Science, 2025)
The Qingjiang Estuary mangrove forest, located at the northernmost edge of China's mangrove belt, plays a vital role in maintaining regional ecological balance. This study aimed to investigate the sources and seasonal dynamics of nitrogen and organic matter across different vegetation zones within the estuary. Sediment samples were collected during summer (June) and autumn (November) and analyzed for total nitrogen (TN), ammonium nitrogen (NH4+-N), nitrate nitrogen (NO3–N), total organic carbon (TOC), and C/N ratios. Stable isotopes (δ13C and δ15N) were used to quantitatively trace nitrogen sources. Principal component analysis (PCA) was employed to assess the influence of sediment physicochemical properties on nitrogen distribution, and Bayesian mixing model analysis was conducted to identify organic matter sources. Spatially, nitrogen and carbon concentrations decreased from west to east across the estuary. Distinct seasonal differences were observed in nitrogen forms and concentrations: TN and NO3–N levels significantly increased in autumn, while NH4+-N remained relatively stable. PCA results revealed that the first principal component (PC1, explaining 37.6% of variance) was dominated by TN, NO3–N, and water content, while the second component (PC2, explaining 18% of variance) was primarily associated with TOC, C/N ratios, and pH. Bayesian mixing model analysis indicated that organic matter primarily originated from terrestrial sources, including C3 and C4 plants, with minor contributions from aquaculture and marine plankton. Average contribution rates were: other terrestrial sources (24.6%) > C3 plants (23.83%) > C4 plants (23.75%) > aquaculture (16.7%) > plankton and marine sources (11.12%). Seasonal shifts in sedimentary environments strongly influenced nitrogen accumulation patterns. These findings provide important insights into nitrogen dynamics and source identification in mangrove ecosystems, contributing to the development of ecosystem management and conservation strategies for this region.